Removal of Heavy-Metal Ions from Aqueous Solutions Using Activated Carbons: Effect of Adsorbent Surface Modification with Carbon Nanotubes - A. Burakov; I. Romantsova; A. Kucherova; A. Tkachev (Adsorption Science & Technology, 2014)
This paper describes the effect of surface nanomodification of porous adsorbents. Two commercial activated carbons (ACs), AG-5 and NWC coconut shell based, were used as adsorbents. The adsorbents were modified with carbon nanotubes (CNTs) by chemical vapour deposition. The CNTs were synthesized in the presence of a metal-oxide catalyst prepared using a citrate solgel method. The concentration of metal ions was evaluated by a spectrophotometric method. Experimental results show that the nanomodification of ACs increased their equilibrium adsorption of heavy metals (Ni 2+ and Co 2+ ) by 10–30%. Besides, the adsorption behaviour of these metal ions on the standard and nanomodified ACs was determined based on adsorption isotherms. A theoretical description of the adsorption mechanism is presented, and equilibrium constants were calculated. Experimental data on the adsorption of the heavy-metal ions on the nanomodified carbons were successfully fitted to the Langmuir and Freundlich models.